An fMRI Study of the Influence of a History of Substance Abuse on Working Memory-Related Brain Activation in Schizophrenia - Wojtalik, Jessica A.; Barch, Deanna M. (Frontiers in Psychiatry, 2014)
There has been little investigation of the effects of past substance abuse (SA) on working memory (WM) impairments in schizophrenia. This study examined the behavioral and neurobiological impact of past SA (six months or longer abstinence period) on WM in schizophrenia. Thirty-seven schizophrenia patients (17 with past SA and 20 without) and 32 controls (12 with past SA and 20 without) completed two versions of a 2-back WM task during fMRI scanning on separate days. Analyses focused on regions whose patterns of activation replicated across both n-back tasks. Schizophrenia patients were significantly less accurate than controls on both n-back tasks. No main effects or interactions with past SA on WM performance were observed. However, several fronto-parietal-thalamic regions showed an interaction between diagnostic group and past SA. These regions were significantly more active in controls with past SA compared to controls without past SA. Schizophrenia patients with or without past SA either showed no significant differences, or patients with past SA showed somewhat less activation compared to patients without past SA during WM. These results suggest robust effects of past SA on WM brain functioning in controls, but less impact of past SA in schizophrenia. This is consistent with previous literature indicating less impaired neurocognition in schizophrenia with SA.